2021
DOI: 10.1038/s41598-021-84036-9
|View full text |Cite
|
Sign up to set email alerts
|

Combination of histochemical analyses and micro-MRI reveals regional changes of the murine cervix in preparation for labor

Abstract: The cervix is responsible for maintaining pregnancy, and its timely remodeling is essential for the proper delivery of a baby. Cervical insufficiency, or “weakness”, may lead to preterm birth, which causes infant morbidities and mortalities worldwide. We used a mouse model of pregnancy and term labor, to examine the cervical structure by histology (Masson Trichome and Picrosirius Red staining), immunohistochemistry (Hyaluronic Acid Binding Protein/HABP), and ex-vivo MRI (T2-weighted and diffusion tensor imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 63 publications
(37 reference statements)
1
1
0
Order By: Relevance
“… 28 , 29 A recent study has shown diffusion MRI images detected changes in tissue organization as gestation progressed suggesting the potential application of this technique to non-invasively monitor cervical changes that precede the onset of labor in women at risk for preterm delivery. 14 Our study is concordant with existing research indicating that MRI is a promising tool to assess the cervix. Women experiencing second-trimester miscarriage are at increased risk in subsequent pregnancies of recurrence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 28 , 29 A recent study has shown diffusion MRI images detected changes in tissue organization as gestation progressed suggesting the potential application of this technique to non-invasively monitor cervical changes that precede the onset of labor in women at risk for preterm delivery. 14 Our study is concordant with existing research indicating that MRI is a promising tool to assess the cervix. Women experiencing second-trimester miscarriage are at increased risk in subsequent pregnancies of recurrence.…”
Section: Discussionsupporting
confidence: 92%
“… 13 Through signal intensity spectroscopy, accurate assessment of the biometry, and individualization of the stromal zone, MRI of the cervix has shown particular morphological features that may signify access to the cervix’s microstructure. 14 In this aspect, exploration of the potential risk factors contributing to miscarriage prior to conception and further setting up of a predictive calculation model with a combination of all the risk factors will be of great importance.…”
Section: Introductionmentioning
confidence: 99%